ANALISIS PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, KEBIJAKAN DEVIDEN DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Muhammad MeikiTriyono, 15.05.52.0366; Wahyu Widati, Lisyorini (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of company size, profitability, dividend policy and investment decisions on firm value in property & real estate companies listed on the Indonesia Stock Exchange in 2015-2017. This research was conducted using secondary data. The population in this study are all property & real estate companies listed on the Indonesia Stock Exchange in 2015-2017. Sampling in this study used a purposive sampling method. The analytical method used in this study is to use multiple regression analysis. The results of the study show that the Company Size variable has a positive and insignificant effect on Firm Value, Profitability has a significant positive effect on Corporate Value, Dividend Policy has a positive and insignificant effect and Investment Decision has a significant positive effect on Firm Value. Adjusted R square value in this study is 0.723, which means that 72.3% of the dependent variable can be explained by the independent variable and the rest explained by other variables outside the model.